Demographic profiling – a determination of academic performance in a Postgraduate Diploma in Marketing Management - Beneke, J; Beeming, C (South African Journal of Higher Education, 2011)
This article analyses the direct effect of demographic variables on academic outcomes. The study concludes that ethnic group plays a pivotal role in determining the academic performance of students registered for the Postgraduate Diploma in Marketing Management at the University of Cape Town. White students (presumed to emanate from a privileged background in most cases) were found to perform strongly whilst black and coloured students (presumed to be from disadvantaged backgrounds in most cases) were considerably more challenged by their studies. Slight variations were recorded for other variables. Here, local students, female students, those emanating from Commerce and Science/Engineering degrees, and those with some work experience performed better than their peers. Performance between Marketing and General Management courses was highly correlated; however both were significantly less correlated with Corporate Finance. The study also finds that students, particularly those from less demanding undergraduate qualifications, tend to find their footing during the first semester and therefore perform better in the second semester of their studies.